A Win–Loss Interaction on Fe0 Between Methanogens and Acetogens From a Climate Lake - Palacios, Paola Andrea; Francis, Warren Russell; Rotaru, Amelia-Elena (Frontiers in Microbiology, 2021)
Diverse physiological groups congregate into environmental corrosive biofilms, yet the interspecies interactions between these corrosive physiological groups are seldom examined. We, therefore, explored Fe0-dependent cross-group interactions between acetogens and methanogens from lake sediments. On Fe0, acetogens were more corrosive and metabolically active when decoupled from methanogens, whereas methanogens were more metabolically active when coupled with acetogens. This suggests an opportunistic (win/loss) interaction on Fe0 between acetogens (loss) and methanogens (win). Clostridia and Methanobacterium were the major candidates doing acetogenesis and methanogenesis after 4 transfers (metagenome sequencing) and the only groups detected after 11 transfers (amplicon sequencing) on Fe0. Since abiotic H2 failed to explain the high metabolic rates on Fe0 we examined whether cell exudates (spent media filtrate) promoted the H2 – evolving reaction on Fe0 above abiotic controls. Undeniably, spent media filtrate generated three to four-fold more H2 than abiotic controls, which could be partly explained by thermolabile enzymes and partly by non-thermolabile constituents released by cells. Next, we examined the metagenome for candidate enzymes/shuttles that could catalyze H2-evolution from Fe0 and found candidate H2-evolving hydrogenases and an almost complete pathway for flavin biosynthesis in Clostridium. Clostridial ferredoxin dependent [FeFe]-hydrogenases may be catalyzing the H2-evolving reaction on Fe0, explaining the significant H2-evolved by spent media exposed to Fe0. It is typical of Clostridia to secrete enzymes and other small molecules for lytic purposes. Here they may secrete such molecules to enhance their own electron uptake from extracellular electron donors but indirectly make their H2-consuming neighbors – Methanobacterium fare 5 times better in their presence. The particular enzymes and constituents promoting H2-evolution from Fe0 remain to be determined. However, we postulate that in a static environment like corrosive crust biofilms in lake sediments, less corrosive methanogens like Methanobacterium could extend corrosion long after acetogenesis ceased, by exploiting the constituents secreted by acetogens.